2016
DOI: 10.1364/ao.55.00d101
|View full text |Cite
|
Sign up to set email alerts
|

Barrier layer induced channeling effect of As ion implantation in HgCdTe and its influences on electrical properties of p–n junctions

Abstract: The HgCdTe layers (xCd∼0.285 and 0.225) were grown by molecular beam epitaxy and liquid phase epitaxy, respectively, followed by the deposition of CdTe and ZnS films as barrier layers by thermal evaporation. Then, the p-on-n photodiodes were fabricated by AS ion implantation, Hg overpressure annealing, passivation, and metallization. The secondary ion mass spectrometry and transmission electron microscopy results indicate that the evaporated CdTe layer with a column structure induces the channeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…The barrier layer is deposited to protect the MCT epilayer from the external contamination and absorb the induced damages. However, the thin evaporated CdTe barrier layer was proved to generate the BLICE effect [13]. This effect can be suppressed by increasing the thickness of evaporated CdTe layer and adopting the other barrier layer materials [12].…”
Section: Ion Beam Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The barrier layer is deposited to protect the MCT epilayer from the external contamination and absorb the induced damages. However, the thin evaporated CdTe barrier layer was proved to generate the BLICE effect [13]. This effect can be suppressed by increasing the thickness of evaporated CdTe layer and adopting the other barrier layer materials [12].…”
Section: Ion Beam Applicationsmentioning
confidence: 99%
“…Some studies on arsenic ion implantation in MCT have been reported in several literature studies [4,8,11] and our previous work [12][13][14]. Classically, SIMS is used to acquire the distribution profiles of implanted ions, while the microstructures and distributions of induced damages are observed by TEM.…”
Section: Introductionmentioning
confidence: 99%
“…Development of the photodiode technology based on ion implantation requires microstructural studies of the implanted material, and arsenic-implanted MCT is not an exception (Mollard et al 2011;Lobre et al 2014;Shi et al 2016;Bonchyk et al 2020). These studies allow for assessing the type and the density of implantation-induced structural defects, which play a key role in controlling the electrical properties of the as-implanted MCT (Lobre et al 2014;Shi et al 2016). Electrical studies, in their turn, allow for assessing the degree of activation of the implanted ions and for obtaining the information on the transport properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the formation of graded-gap CdTe layer on MCT epilayer is significant for the acquisition of high-quality surface passivation. In our previous work [7,8], the influences of CdTe and ZnS cap layer microstructures on the implanted ion distributions and diffusions in MCT epilayers were studied. Here, the research work is focused on the CdTe/MCT structures, which is prepared by depositing CdTe cap layers onto MCT substrates by magnetron sputtering and thermal evaporation.…”
Section: Introductionmentioning
confidence: 99%